Poly(methylhydrosiloxane) as a green reducing agent in organophosphorus-catalysed amide bond formation. Issue 30 (24th July 2017) - Hamstra, Daan F. J.; Lenstra, Danny C.; Koenders, Tjeu J.; Rutjes, Floris P. J. T.; Mecinović, Jasmin
Abstract : In situ reduction of phosphine oxide by poly(methylhydrosiloxane) leads to efficient amidation reaction between carboxylic acids and amines. Abstract : Development of catalytic amide bond formation reactions has been the subject of the intensive investigations in the past decade. Herein we report an efficient organophosphorus-catalysed amidation reaction between unactivated carboxylic acids and amines. Poly(methylhydrosiloxane), a waste product of the silicon industry, is used as an inexpensive and green reducing agent for in situ reduction of phosphine oxide to phosphine. The reported method enables the synthesis of a wide range of secondary and tertiary amides in very good to excellent yields.